NOVOS MODELOS DE PRODUÇÃO MUSICAL E CONSUMO: Um estudo sobre as mudanças ocorridas com o advento das plataformas digitais - Araújo, Valterlei Borges de (2011)
Recent changes in the music market, especially from the development and popularization of the internet, have changed substantially the current models involving the music business. From the old model, driven by major labels, we started a new era, still full of uncertainties, however, recasting the whole picture and opens up a range of possibilities for musicians who are out of the big circuit, mainly from the varied channels of communication available on the network via new media platforms. The vision of musicians that are being built from these tools, as well as the vision of the music industry itself, shows us what is at stake with these changes, which among other things stand out: readjustment of the whole sociocultural system involving the supply chain and cultural industry and the framing of current discussions around the economy and cultural production, which often turns out to produce a new approach to cultural studies and contemporary cultural criticism. As results, we conclude that indeed the changes highlighted from the popularization of the Internet and digital tools are reshaping the entire system of the recording industry. The legacy of decades of previous business model brings very strong practices and possibly still take considerable time to be abandoned. This transformation has been hindered, because we are still adjusting ourselves to these changes and still there is no one model that serves as a key basis for this new market reality